Literature Review: Image Processing-Based Forest Fire Detection - Ihkram, Sejaratuh Ihkram Mulya (Rumah Jurnal, 2024)
-Forest fires pose a significant threat to ecosystems, the environment, and human life. Early detection of forest fires is crucial for effective firefighting efforts. In this research, we propose the utilization of image processing for forest fire detection with the aim of improving rapid and accurate response in fire monitoring. Image processing methods are employed to analyze visual information obtained from satellite imagery, drones, or other sensors. The process involves image segmentation, classification, and texture analysis to identify the burned areas. Fire point detection algorithms are implemented to monitor and predict fire propagation. Through image processing, we achieved faster and more accurate forest fire detection. The information gathered from the images can be used to report real-time fire development and facilitate effective firefighting strategies. The adoption of this technology offers advantages in reducing environmental damage, economic losses, and risks to human life.